Early tibial loosening of the cemented ATTUNE knee arthroplasty: just a question of design? - Jäger, Sebastian; Eissler, Marvin; Schwarze, Martin; Schonhoff, Mareike; Kretzer, Jan Philippe; Bitsch, Rudi G. (The knee, 2021)
Background - Total knee arthroplasty is a very successful standard treatment for severe osteoarthritis. Nevertheless, the literature reports tibial debonding between implant and bone cement as well as radiolucent lines related to the tibial components of different knee systems. Regardless of cementing techniques and the influences during surgery, we examined the design of a newly developed knee system and its predecessors (Attune, Attune S+, P.F.C. Sigma, P.F.C. Sigma RP/M.B.T., all DePuy). - Methods - We investigated the dimensions of the tibial components and the fit between them and their bone bed after instrumentation in a foam material. - Results - Our results showed considerable differences for the used knee prostheses as well as their tibial instrumentation options with a corresponding risk for incomplete seating. - Conclusion - The orthopedic surgeons need to be aware of these design features and the resulting increased seating resistance especially in hard and sclerotic bone. - Article focus - Comparison of the tibial instruments and the different design options of the Attune knee system and its predecessor knee prostheses. - Key messages - The Attune implant showed incomplete seating because of too much press fit and an uneven bone quality or sclerosis can result in tilting of the tibial component. - Strengths and limitations - This is the first study investigating the Attune knee and its predecessor in terms of implant seating and press fit. The foam material is a limitation.
Gesehen am 14.07.2021